Chemotherapy Patients' Pain Levels and Their Ability to Perform Activities of Daily Living (Adl) - Merbawani, Raras (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Chemotherapy induces pain in individuals with cancer, leading to various physical consequences such as fatigue, reduced appetite, vomiting, and compromised muscle strength. As a consequence of this effect, activities of daily living (ADL) are disrupted. The purpose of this study was to determine the relationship between pain intensity and capacity to perform activities of daily living (ADL) among chemotherapy patients in the Bangil Pasuruan Regional Hospital's Chemotherapy Room. This study employs a correlational design and a cross-sectional methodology. All 31 chemotherapy patients in the Chemotherapy Room at Bangil Pasuruan Regional Hospital comprised the population of this investigation. Utilizing consecutive sampling, a sample of twenty-three individuals was collected between April 15 and May 15, 2023. The investigation utilized the Barthel index and numeric pain scale as its instruments. For data analysis, the Spearman Rho Test was utilized. 18 respondents (78.3%) reported experiencing moderate discomfort, and the majority of respondents (15 respondents, or 65.2%) reported having mild ADL abilities, according to the findings of the study. The Spearman test yielded a p-value of 0.0 and a correlation coefficient of 0.722; therefore, H 1 is accepted. This indicates that there is a significant relationship between the intensity of pain and the ability of chemotherapy patients to perform activities of daily living (ADL) in the Chemotherapy Room at Bangil Pasuruan Regional Hospital. Specifically, as the intensity of the pain increases, so does the degree of dependence of the patients on ADL. A decrease in muscle strength brought on by pain diminishes the ability to perform ADLs. It is the responsibility of hospital nurses to assist chemotherapy patients with activities of daily living (ADLs) and to instruct them in non-pharmaceutical relaxation and distraction techniques to alleviate discomfort.